THE CONTRIBUTION OF BAR TWIST EXERCISES ANDTRAINING ON SIGNAL ACOUSTIC UPPER SERVICE ABILITY IN SEPAK TAKRAW ATHLETES IN NORTH SUMATRA - Akram Muhibulloh Bangko; Amir Supriadi; Budi Valianto (Indonesia Sport Journal, 2020)
This study aims to determine the contribution of bar twist training and training. signal acoustic on top serviceability. The population in this study were all sepak takraw athletes from North Sumatra, which amounted to 12 people. The number of samples of 9 people was obtained by the purposive sampling technique. The instruments used in this study were the instrument sit and reach to measure the flexibility of the waist muscles, the instrument whole-body reaction which aimed to measure reaction speed with the serve ability instrument on sepak takraw. The results of the analysis of the first hypothesis show that there is a significant contribution to training bar twist on serviceability with a value of (2.69 > 1.895). The results of the analysis of the second hypothesis showed that there was no significant contribution to the training acoustic signal on serviceability with a value of (3.48 <5.14). From the results of hypothesis testing, it can be concluded that there is no significant contribution of bar twist training and training acoustic signal to the ability of the top service in sepak takraw athletes in North Sumatra.Keywords: Bar Twist, Acoustic Signal, Top Serviceability